Long-Term Outcome of Transcatheter Device Closure of Perimembranous Ventricular Septal Defects - Krishna D. Mandal; Danyan Su; Yusheng Pang (Frontiers Media S.A., 2018)
Background: Ventricular septal defect is a common congenital heart defect. Transcatheter closure of perimembranous ventricular septal defect (pmVSD) is an effective method alternative to surgical closure. The aim of the study is to evaluate the procedural result, early and long-term follow-up outcome of transcatheter closure of pmVSD.Methods: From January 2005 to December 2016, we retrospectively identified the patients who underwent transcatheter device closure of pmVSD. All patients underwent transthoracic echocardiography (TTE) and electrocardiogram (ECG) before and after the procedure. Follow-up evaluation was done at 1, 3, 6, 12 months and yearly thereafter with TTE and ECG.Results: Total 186 patients (95 male, 91 female) had catheter-based intervention of pmVSD. The mean age at the time of procedure was 5.4 ± 2.8 years (range 2~14 years) and the mean weight was 18.1 ± 6.7 kg (range 10.5~43 kg). The mean size of the implanted device was 8.4 ± 2.1 mm (range 5~16 mm). The device was successfully implanted in 180 patients (96.8%). Immediate post-procedural echocardiography showed complete occlusion in all but one patient had trivial residual shunt. Total early adverse events occurred in 16 patients (8.9%). Only in two patients it was significant, complete AVB occurred in a 9 years old boy, managed with temporary pacemaker and one patient had complete left bundle branch block, recovered fully after steroid therapy. During a median follow-up period of 18.4 months (range 6~120 months), no serious adverse events and complete AVB were encountered.Conclusion: In our experience, The incidence of serious adverse event is low and no late onset of complete AVB with excellent success rate and follow-up results, confirming the transcatheter closure of pmVSD is a valuable alternative to surgical closure in selected patients.